(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Palshkova I. О. Teacher education in the context of current humanistic educational paradigm. The human orientation of educational content at higher schools is implemented through complex personality development with the help of pedagogical disciplines, provided with the system of pedagogic conditions among which the following should be mentioned: creating situations of achieving success in cognitive activity; implementing the differentiated approach to forming the content of students’ training activity; organizing group forms of cognitive activity based on co-authorship and co-operation in the system “teacher-to-student”; including pupils in educational games developed on timely material.